Transition-Metal-Free, Potassium tert-Butoxide/Dimethyl Sulfoxide Mediated Amination between Tertiary Amines and Aryl Halides - Huang, Pei; He, Bang-Yue; Wang, Hui-Min; Lu, Jian-Mei (Synthesis, 2015)
A transition-metal-free, C–N bond-formation reaction between tertiary amines and aryl halides is reported. Under the optimal conditions, various aromatic and aliphatic tertiary amines react with aryl halides, including iodides, bromides, and chlorides, to give mono-aminated products, N,N-dialkylanilines and N-alkyl-N-arylanilines, in good to high yields. Based on the experimental results, the reaction is believed to occur via an aryne intermediate derived from the aryl halide.
Keywords: transition-metal-free; tertiary amines; aryl halides; amination reaction; synthetic method